Food Safety Study of Petis Crackers in Kendal Regency, Central Java - Akhmad Mustofa; Nanik Suhartatik; Gigih Pranata; Ridofan Aji Pradana (Jurnal Ilmu Pertanian Indonesia, 2025)
Food safety is a science that deals with preparing, managing, and storing food or beverages to be safe from physical, biological, and chemical contamination. The processing of petis (condiments of fermented fish or shrimp) crackers is one of the categories of SMEs in Kendal Regency, Central Java. The study aimed to evaluate the heavy metals of iron (Fe), lead (Pb), and other chemical features and to survey the processing of petis crackers. This is a descriptive study of an observational nature with a quantitative approach, especially by doing laboratory observations. The study also carried out qualitative observations using questionnaires regarding the manufacturing of petis crackers. Petis is food or items cooked in a thick, clayey, and elastic condiment group. The results showed that Fe levels vary from 48.00 to 82.00 mg/kg and Pb from 40.00 to 50.00 mg/kg. The average chemical properties of the petis crackers are as follows: 2.45% ash, 13.27% moisture, 3.13% protein, 0.15% fat, and 81.0%carbohydrate. The lead content surpasses the maximum limit of the standard set by the BPOM (The Indonesian Food and Drug Supervisory Agency). Keywords: food safety, heavy metal, Kendal, petis crackers